Modeling, Simulation and Optimization of Complex Processes HPSC 2015: Proceedings of the Sixth International Conference on High Performance Scientific Computing, March 16-20, 2015, Hanoi, Vietnam - Bock, Hans Georg; Phu, Hoang Xuan; Rannacher, Rolf; Schlöder, Johannes P. (Springer, 2017)
This proceedings volume highlights a selection of papers presented at the Sixth International Conference on High Performance Scientific Computing, which took place in Hanoi, Vietnam on March 16-20, 2015. The conference was jointly organized by the Heidelberg Institute of Theoretical Studies (HITS), the Institute of Mathematics of the Vietnam Academy of Science and Technology (VAST), the Interdisciplinary Center for Scientific Computing (IWR) at Heidelberg University, and the Vietnam Institute for Advanced Study in Mathematics, Ministry of Education The contributions cover a broad, interdisciplinary spectrum of scientific computing and showcase recent advances in theory, methods, and practical applications. Subjects covered numerical simulation, methods for optimization and control, parallel computing, and software development, as well as the applications of scientific computing in physics, mechanics, biomechanics and robotics, material science, hydrology, biotechnology, medicine, transport, scheduling, and industry
Keywords: Konferenzschrift